SPE/IADC Middle East Drilling Technology Conference 1999
DOI: 10.2118/57579-ms
|View full text |Cite
|
Sign up to set email alerts
|

A New Hydraulics Model for Slim Hole Drilling Applications

Abstract: A model to predict the pressure loss for slim hole drilling has been constructed. The model, which is constructed by theoretical and numerical analysis and experimental measurements, incorporates the effect of eccentricity, drillstring rotation and rheology. Introduction Slim-hole drilling has been pursued in the last decade as a mean to drill exploration wells with a minimum of logistic support. Slimming down the well design will also give a cheaper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…It should be noted that the eccentricity and rotation of the drill string are two factors that cannot be ignored in the calculation of the annular pressure drop in HW-SH, 33,34 and therefore, the calculation method of the friction pressure drop based on the conventional pipe model is no longer applicable. Here, correction factors of pressure k 1 and k 2 were added to the model to calculate the annular pressure loss of HW-SH more accurately.…”
Section: Shear Stresses For Each Layermentioning
confidence: 99%
“…It should be noted that the eccentricity and rotation of the drill string are two factors that cannot be ignored in the calculation of the annular pressure drop in HW-SH, 33,34 and therefore, the calculation method of the friction pressure drop based on the conventional pipe model is no longer applicable. Here, correction factors of pressure k 1 and k 2 were added to the model to calculate the annular pressure loss of HW-SH more accurately.…”
Section: Shear Stresses For Each Layermentioning
confidence: 99%
“…pi pi po po pi po pi dp (14) For the area inside the drill column, the heat sources were fluid axial heat transfer, frictional heat generation, and heat transfer from the outer to the inner wall of the drill column. The increment in the fluid axial heat transfer ∆t is…”
Section: Assumptionsmentioning
confidence: 99%
“…In addition to considering the drilling column rotation, he also considered the effect of the eccentricity of the drilling column and the variability of its eccentricity along the wellbore axial direction on the annular pressure dissipation and developed a new model for the annular pressure dissipation in HW‐SH. Hansen 14 concluded that the mud type plays an important role in predicting HW‐SH annular pressure depletion and proposed a model for calculating HW‐SH annular pressure depletion for Newtonian, Bingham, and power‐law fluids. However, the calculation process is complicated and cumbersome and cannot be extended to other applications.…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, Haciislamoglu and Cartalos [13] provided the corresponding prediction models of the pressure losses for the laminar flow, transition flow, and turbulent flow. Starting from analysis of the friction factor, Hansen et al [14] established the theoretical model about the frictional pressure loss for different flow regimes. Hashemian et al [15] proposed a prediction model for the frictional pressure loss of the Yield-Power-Law fluid flowing in the annular region.…”
Section: Introductionmentioning
confidence: 99%